Melukat; a purification by water - Yogi Meranggi (Bali Tourism Board, 2018)
Balinese practices an ancient method to neutralize negative energies in someone’s mind. the forefather passed the method from one to other generations. strongly influenced by Hinduism, it is used not only for mental wellness but also for balance spiritual life. The method is commonly referred by locals as ‘Melukat’. in Hinduism literatures, such as Atharva Veda and Rig Veda, purification ritual by using water mentioned in several hymns. It aims to cleanse and purify someone from ‘stain’ they may obtain from a previous life, as a consequence of their actions or even other person deeds. water has power of bhutakhas, chitakhas, and chudaakhas, to cleanse and neutralize sin. the suitable places for melukat are mountains, the meeting of two rivers (campuhan), the source of the springs, the sea or a tranquil place. Those sacred places are believed emanating positive vibe. in addition, coconut water has similar properties as holy water that may be utilized for the ritual. To maximize the result, it is suggested to conduct the ritual on certain days, which is suitable for worship. Due to its function to gain goodness and safety, then the melukat ceremony may be done not only for Hindus but also for everyone, as long as they follow the correct steps in performing the ritual.